The implication of servicescape, emotion and trust to a positive customer service experience: wellness spa context in the U.S.A. / Hyeyoon Choi, Jay Kandampully and Kathryn Stafford - choi,, hyeyoon; Kandampully, Jay; Stafford, Kathryn (Universiti Teknologi MARA Cawangan Sarawak, 2016)
This article examined the antecedents of a positive wellness service experience by identifying factors leading to customers’ positive wellness service experience. This study proposes that servicescape has a positive relationship with the service experience, and that servicescape may strengthen the effects of emotion and trust. The research hypotheses were tested with data collected directly from customers of a spa located in the Midwestern United States. A multiple regression analysis was conducted to estimate how emotion, trust, and servicescape affect customers’ evaluations of spa experiences. An estimation was carried out on the interaction effects between servicescape, emotion and trust. The results indicate that the main effects of servicescape, emotion and trust, were significant, while the interaction effects did not prove to be significant. Trust has the biggest effect on customers’ wellness experience followed by emotion and servicescape. Prior research has not simultaneously addressed the role of servicescape, emotion and trust and their subsequent influence on customers’ emotional evaluation of service experience. This study therefore provides valuable insight to extend present understanding of the simultaneous role of these factors as effective predictors of the evaluation of service experience